MSMEs performance and competitive advantage: Evidence from women's MSMEs in Indonesia - Evi Susanti; Rita Yuni Mulyanti; Lela Nurlaela Wati (Cogent Business & Management, 2023)
This study intends to examine how competitive advantage mediates the effects of digital transformation and innovation on the performance of women-owned MSMEs. A sample of 246 MSMEs in Indonesia run by women was used in this study. To analyze the data, a structural equation model (SEM) was applied. The study's findings indicate that the performance of women-owned MSMEs is not directly impacted by digital transformation. It does have an impact on innovation and competitive advantage. Innovation and competitive advantage can boost women's MSMEs' performance and play a mediating role in Indonesia's digital transformation of women's MSMEs. The study's findings also confirm and broaden the RBV's assertions on the importance of innovation in determining women's MSMEs' competitive advantage. This empirical evidence can be the basis for the government's efforts to encourage the digitization and innovation of women's MSMEs. Research that discusses the competitive advantages of MSME women to performance, digital transformation, and innovation, which is still limited, this study offers a model of the performance of MSME women in developing countries.
Keywords: 650; competitive advantage; digital transformation; innovation; women's MSMEs performance